2018
DOI: 10.1002/cbdv.201800110
|View full text |Cite
|
Sign up to set email alerts
|

Selected Cardoon (Cynara cardunculus L.) Genotypes Suitable for PDO Cheeses in Mediterranean Regions

Abstract: Cardoon flower extract is a traditional and exclusive rennet used for some PDO cheeses in several Mediterranean regions, due to its extremely high concentration in cardosins. In this preliminary study, six individual cardoon genotypes (1M - 6M) were selected because they revealed a wide and consistent diversity of total and specific cardosin concentrations in flowers. During three growing seasons, the stability of 12 biochemical characteristics of flower extracts and 26 plant morphological descriptors was conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Innovations are also associated with the possibility to manipulate the final texture/sensory profile of Serra da Estrela cheese mainly via the thistle ecotype selected (Correia et al, ; Guiné et al, ). The genotype evaluation of selected cardoons has been performed in order to improve the quality and standardization of cardosin profiles from cardoon flowers used for cheese production (Barracosa, Rosa, Barros, & Pires, ), having the different cardoon cultivars been morphologically evaluated (Barracosa, Oliveira, Barros, & Pires, ). Other ways of innovation are the conversion of this traditional cheese into a functional food.…”
Section: Innovation Concerning Serra Da Estrela Cheesementioning
confidence: 99%
“…Innovations are also associated with the possibility to manipulate the final texture/sensory profile of Serra da Estrela cheese mainly via the thistle ecotype selected (Correia et al, ; Guiné et al, ). The genotype evaluation of selected cardoons has been performed in order to improve the quality and standardization of cardosin profiles from cardoon flowers used for cheese production (Barracosa, Rosa, Barros, & Pires, ), having the different cardoon cultivars been morphologically evaluated (Barracosa, Oliveira, Barros, & Pires, ). Other ways of innovation are the conversion of this traditional cheese into a functional food.…”
Section: Innovation Concerning Serra Da Estrela Cheesementioning
confidence: 99%
“…The variability of thistle populations is not limited to morphological characteristics; it has also been observed in the AP content of the flowers. The evaluation of individual genotypes showed that the observed biodiversity is also reflected in the amount and type of APs present in the flowers of each genotype, with enzymes present in some genotypes and absent in others [16]. This variability was also found to affect the milk-clotting process, as the use of flower extracts from different thistle populations displayed different milk-clotting times, which ultimately affected cheese manufacturing and the rheological and sensorial characteristics of the final product [17,18].…”
Section: The Thistle Flower and The Impact Of Its Variability On Milkmentioning
confidence: 99%
“…Triangles indicate glycosylation sites. Based on References[14][15][16] and UniProt KB accession Q9XFX3 and Q9XFX4.…”
mentioning
confidence: 99%
“…Due to their high content of aspartic proteases, and high milk‐clotting activity the cardoon extracts create specific characteristics of texture and flavor . In the case of ‘Serra da Estrela’ cheese, C. cardunculus has actually been recognized as a key factor in cheese authenticity, as defined in an integrated project (CARDOP) designed to promote its protected designation of origin …”
Section: Introductionmentioning
confidence: 99%
“…Achenes can be used not only for biofuel production and bioplastics but also for oil suitable for human consumption due to its high nutritional value . Oil content ranged from 14.5 % to 32.4 % of dry matter depending of the cardoon population and on the extraction method . It can be used in ruminant nutrition as green forage for livestock or preserved as silage, with high organic matter digestibility .…”
Section: Introductionmentioning
confidence: 99%